2021
DOI: 10.1111/epi.16967
|View full text |Cite
|
Sign up to set email alerts
|

Seizure detection using wearable sensors and machine learning: Setting a benchmark

Abstract: Objective Tracking seizures is crucial for epilepsy monitoring and treatment evaluation. Current epilepsy care relies on caretaker seizure diaries, but clinical seizure monitoring may miss seizures. Wearable devices may be better tolerated and more suitable for long‐term ambulatory monitoring. This study evaluates the seizure detection performance of custom‐developed machine learning (ML) algorithms across a broad spectrum of epileptic seizures utilizing wrist‐ and ankle‐worn multisignal biosensors. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 49 publications
(109 reference statements)
1
61
0
1
Order By: Relevance
“…The algorithm was trained on 60-s data segments selected from each recording. To ensure the algorithm was performing seizure forecasting rather than early seizure detection, and to account for potential misalignment between the clocks in the wearable and implanted devices and the potential inexact timing of the seizure onset recorded by the device 26 , 27 , one-hour preictal data epochs were defined with a set-back of 15 min before the seizure onset recorded by the implanted EEG device. Lead seizures were defined as seizures separated from preceding seizures by at least 4 h, and clustered (i.e., non-lead) seizures were excluded from analysis to avoid artificially inflating results.…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm was trained on 60-s data segments selected from each recording. To ensure the algorithm was performing seizure forecasting rather than early seizure detection, and to account for potential misalignment between the clocks in the wearable and implanted devices and the potential inexact timing of the seizure onset recorded by the device 26 , 27 , one-hour preictal data epochs were defined with a set-back of 15 min before the seizure onset recorded by the implanted EEG device. Lead seizures were defined as seizures separated from preceding seizures by at least 4 h, and clustered (i.e., non-lead) seizures were excluded from analysis to avoid artificially inflating results.…”
Section: Methodsmentioning
confidence: 99%
“…At present, a clear evidence gap has still to be filled before introducing the automated ambulatory detection of nonconvulsive seizures into clinical practice (28,78,79). However, promising results using the E4 wristband indicated that this may be possible with a wrist-worn device (80)(81)(82). Additionally, advanced post-processing analytics on the peri-ictal periods may provide seizure semiology information, thereby expanding the quality of available patient data.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Of the included studies, six were included for meta-analysis [17,18,[25][26][27][28]. The remaining 13 studies [19,20,[29][30][31][32][33][34][35][36][37][38][39] were only considered for qualitative analysis, as they did not report the frequency of seizures with an EDA response.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…The nineteen studies included a total of 550 participants (46% male, 44% female, 10% not recorded), and 1115 recorded seizures. Five studies [28,31,37,40,41] included both adult and pediatric populations, four [19,26,27,29] included only adults, with another six [17,18,20,34,38,39] including only children or young adults. Four studies [30,32,33,35] did not report the age of participants.…”
Section: Summary Of Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation